2017
DOI: 10.1136/bmj.j2423
|View full text |Cite|
|
Sign up to set email alerts
|

New chapter in tackling antimicrobial resistance in Thailand

Abstract: Nithima Sumpradit and colleagues describe the experience of Thailand in developing its national strategic plan on antimicrobial resistance and highlight the need for sustained political commitment and multisectoral collaboration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 2 publications
0
45
0
Order By: Relevance
“…It is recognised that AMR can develop and spread rapidly in regions where antibiotics are inappropriately sold/used and freely available, and that hospital settings provide excellent opportunities for the dissemination of resistance. In Thailand, carbapenem-resistant P. aeruginosa is an increasing problem, especially in the context of hospital-acquired infections (8,9) . Previous studies have sought to characterise the genetic basis underlying carbapenem resistance amongst P. aeruginosa clinical isolates in Thailand (10) , and globally (11) , but the role of plasmids is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is recognised that AMR can develop and spread rapidly in regions where antibiotics are inappropriately sold/used and freely available, and that hospital settings provide excellent opportunities for the dissemination of resistance. In Thailand, carbapenem-resistant P. aeruginosa is an increasing problem, especially in the context of hospital-acquired infections (8,9) . Previous studies have sought to characterise the genetic basis underlying carbapenem resistance amongst P. aeruginosa clinical isolates in Thailand (10) , and globally (11) , but the role of plasmids is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is recognised that AMR can develop and spread rapidly in regions where antibiotics are inappropriately sold/used and freely available and that hospital settings provide excellent opportunities for the dissemination of resistance. In Thailand, carbapenem-resistant P. aeruginosa is an increasing problem, especially in the context of hospital-acquired infections 8 . Previous studies have sought to characterise the genetic basis underlying carbapenem resistance among P. aeruginosa clinical isolates in Thailand 9 , and globally 10 , but the role of plasmids is poorly understood.…”
mentioning
confidence: 99%
“…Despite the fact that most URTIs have viral aetiology, therefore antibiotics are not usually indicated and when used they have neither cured (reduced the symptoms/prevented complications) nor shorten the duration of URTIs [20]. We found that considerable number of patients still received antibiotics for URTIs at ETU.…”
Section: Discussionmentioning
confidence: 72%